2024
DOI: 10.1108/jgoss-12-2023-0106
|View full text |Cite
|
Sign up to set email alerts
|

Role of information processing and digital supply chain in supply chain resilience through supply chain risk management

Aamir Rashid,
Rizwana Rasheed,
Abdul Hafaz Ngah
et al.

Abstract: Purpose Supply chain (SC) management is more challenging than ever. Significantly, the pandemic has provoked global and economic destruction that appeared in the manufacturing industry as a “black swan.” Therefore, the purpose of this study was to examine the role of information processing and digital supply chain in supply chain resilience through supply chain risk management. Design/methodology/approach This study examines SC risk management and resilience from an information processing theory perspective.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…Emerging research areas were identified by using structural topic modelling (STM). Rashid et al (2024aRashid et al ( , 2024b findings illustrated that green supply chain practices positively influence all used variables and provided a practical insight to practitioners to implement green practices in their supply chain networks for social, economic and environmental sustainability and compliance with SDG-12 and SDG-13. Rashid et al (2024aRashid et al ( , 2024b) also found that information processing capability and digital SC significantly and positively affect SC risk management and resilience.…”
Section: Manuscript Title Authormentioning
confidence: 91%
See 2 more Smart Citations
“…Emerging research areas were identified by using structural topic modelling (STM). Rashid et al (2024aRashid et al ( , 2024b findings illustrated that green supply chain practices positively influence all used variables and provided a practical insight to practitioners to implement green practices in their supply chain networks for social, economic and environmental sustainability and compliance with SDG-12 and SDG-13. Rashid et al (2024aRashid et al ( , 2024b) also found that information processing capability and digital SC significantly and positively affect SC risk management and resilience.…”
Section: Manuscript Title Authormentioning
confidence: 91%
“…Rashid et al (2024aRashid et al ( , 2024b findings illustrated that green supply chain practices positively influence all used variables and provided a practical insight to practitioners to implement green practices in their supply chain networks for social, economic and environmental sustainability and compliance with SDG-12 and SDG-13. Rashid et al (2024aRashid et al ( , 2024b) also found that information processing capability and digital SC significantly and positively affect SC risk management and resilience. Also, supply chain risk management positively mediates the relationship between information processing capability and digital SC.…”
Section: Manuscript Title Authormentioning
confidence: 91%
See 1 more Smart Citation
“…The supply chain business activities are disrupted, causing the coronavirus outbreak. The economic system and society are the veins of supply chain operations (Ivanov, 2020;Rashid et al, 2024c). Businesses at some stage in the world have confronted unparalleled demanding situations because of disruptions caused by the outbreak and shutdown.…”
Section: Role Of Logistics Innovation Capabilities In Supply Chains O...mentioning
confidence: 99%
“…Efficient and effective supply chain management (SCM) plays a pivotal role in ensuring the smooth flow of raw materials from suppliers to manufacturing firms, ultimately producing final goods. Therefore, organizations must focus on the supplier side to achieve sustainability goals (Rashid et al, 2024c). Sarkis (2003) observes that companies increasingly integrate environmental practices into their strategic plans.…”
mentioning
confidence: 99%